2014
DOI: 10.1162/rest_a_00426
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving to Elderly Parents and Employment Status of European Mature Women

Abstract: Internet: www.cemfi.es We would like to thank Olympia Bover and Agar Brugiavini for insightful discussions and Manuel Arellano and Stephane Bonhomme for useful conversations. This work also benefited from the comments of seminar participants at AbstractWe study the prevalence of informal caregiving to elderly parents by their mature daughters in Europe and the effect of intense (daily) caregiving and parental health on the employment status of the daughters. We group the data from the first two waves of SHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 22 publications
6
104
2
1
Order By: Relevance
“…When the daughter responds to the parent's need for care, any frequency, weekly, and daily caregiving reduces the probability that the daughter is employed by 34, 37, and 60 percentage points, respectively, in family care countries, while caregiving in formal care countries has no effect on caregivers' employment probability. The large effect found for family care countries and the absence of an effect in formal care countries is in line with the finding by Crespo and Mira (2010) who find a 50% drop in the employment probability in Southern European countries and no change for Northern European countries but contradicts studies that find no or only negligible effects in all countries as well as studies that report negative effects in Northern European countries. 32 As mentioned above, the FE-IV regressions for hours worked suffer from weak instrument problems and results are only shown for completeness.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…When the daughter responds to the parent's need for care, any frequency, weekly, and daily caregiving reduces the probability that the daughter is employed by 34, 37, and 60 percentage points, respectively, in family care countries, while caregiving in formal care countries has no effect on caregivers' employment probability. The large effect found for family care countries and the absence of an effect in formal care countries is in line with the finding by Crespo and Mira (2010) who find a 50% drop in the employment probability in Southern European countries and no change for Northern European countries but contradicts studies that find no or only negligible effects in all countries as well as studies that report negative effects in Northern European countries. 32 As mentioned above, the FE-IV regressions for hours worked suffer from weak instrument problems and results are only shown for completeness.…”
Section: Resultssupporting
confidence: 84%
“…Ciani (2012) finds small or insignificant negative effects on employment of co-residential caregiving, with a slightly larger effect in Southern European countries in some specifications, while Viitanen (2010) finds caregiving only significantly reduces women's employment probability in Germany. 4 Contrary, Crespo and Mira (2010) find a negligible effect of daily parental caregiving on employment in Northern and Central European countries but a 50% decline in the employment probability in Southern European countries. Looking at cross-sectional data, Bolin et al (2008b) find a negative effect on hours worked in Central European countries, but no effect on employment, whereas Crespo (2006) finds caregiving reduces women's probability of employment by 30-40% with slightly more adverse effects in Central Europe than in Southern Europe.…”
Section: Background and Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, intensive caregiving (defined in various ways) often has a stronger effect on employment or hours of paid work than low-frequency or no caregiving. The largest effect on employment is found by Crespo and Mira (2014). They find that, for southern European women that provide daily caregiving because of parental disability, daily caregiving implies a 45-65% decrease of the probability of being employed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Labor supply reactions (of females, mostly) have been studied by, e.g., Carmichael and Charles (1998), Heitmueller (2007), Ciani (2012), Casado-Marín et al (2011), Bolin et al (2008), Ettner (1995Ettner ( , 1996, Crespo and Mira (2014), Heger (2014), Meng (2012a,b), where the effects range from small to very large (up to 30 percentage points) reductions in the probability to work for pay. 1 The effect on working hours, as studied by, e.g., Wolf and Soldo (1994), Casado-Marín et al (2011), Bolin et al (2008), Ettner (1996), Johnson and Sasso (2000), and Van Houtven et al (2013) are quite mixed, while wage penalties are more consistently found (Van Houtven et al, 2013, Carmichael and Charles, 2003, Heitmueller and Inglis, 2007.…”
Section: Introductionmentioning
confidence: 99%